Forest tourism development conflict analysis under carbon peak and neutrality goals—Based on graph model for conflict resolution - Zhao, Rongrong; Chen, Qiuhua; Kong, Deyi; Song, Yijing (Frontiers in Environmental Science, 2022)
To achieve carbon peaking and carbon neutrality goals, maintaining forest savings has become the key. How to reduce the damage of forest tourism development to the environment, reconcile conflicts, and promote the orderly implementation of forest tourism projects while maintaining forest savings is an important prerequisite for the development and construction of forest tourism. First, we constructed a fundamental Graph Model for Conflict Resolution (GMCR) during forest tourism development under carbon peak and neutrality goals. From the perspective of the dynamic interaction of conflict analysis, this article explains the game behavior behind the conflict of forest tourism development. Next, we calculated the equilibrium solution of a three-party game which means tourism enterprises adopt compensatory strategies, local residents support forest tourism development, and the government supports tourism enterprises for development projects, develops an ecological compensation system, and strengthens supervision. It provides a set of systematic and effective conflict analysis tools for stakeholders of forest tourism development projects and provides decision-making and reference information for the formulation of similar environmental resource development policies.